Morpho-topological investigation of the mechanisms and kinetic regimes of alite dissolution. (October 2015) - Juilland, P.; Gallucci, E.
Abstract: The pure dissolution of alite MIII polymorph under various flow conditions and initial calcium hydroxide concentrations was investigated in a designed flow through dissolution cell. Dissolution profiles and their associated dissolution rates were measured using vertical scanning interferometry (VSI). Two main characteristic features were observed: the rate of dissolution decreases non-linearly with the amount of calcium hydroxide in the initial solution composition and a transition of rate limiting factor occurs for a threshold undersaturation of alite. This behaviour is deduced from the dependency of the rate of dissolution with the flow rate which decreases drastically at low undersaturation level and further supported by the determination of apparent activation energies of dissolution. The study is complemented with surface imaging of dissolution front from samples submitted to different experimental conditions.